Einstellungen zum Flipped-Classroom-Konzept von Nachhilfeschülerinnen und Nachhilfeschülern in Mathematik (mathematica didactica, 2024)
This article analyzes what beliefs tutoring students in secondary school have about the concept of Flipped Classroom in mathematics after having taken part in an intervention based in this concept. The main focus is set on lower-performing learners, a group of individuals considered potentially problematic in previous research. For this goal, interview data are analyzed using a qualitative content analysis, the categories are presented as a contrasting case analysis and finally the categories were discussed with reference to the literature. The results indicates that the tutoring students recognize and list many didactic potentials of the concept. In addition, aspects are mentioned which have not yet been discussed in the literature, such as the influence of personality traits (like introver-sion or extroversion) on the success in learning according to the Flipped Classroom concept.